Subcutaneous basidiobolomycosis treated successfully with oral itraconazole: A case report - Dixit G Chaudhari; Ashish Jagati; Raju G Chaudhary; Malhar J Shah (Wolters Kluwer Medknow Publications, 2022)
Basidiobolomycosis is an opportunistic fungal infection with a high morbidity and mortality rate. It is known to cause invasive disease in immunocompromised persons but it may produce only cutaneous or subcutaneous infections in an immunocompetent patient. Treatment is difficult due to its fulminant course and lack of effective anti-fungal drugs. But here, we report a rare case of Basidiobolomycosis detected in an immunocompetent patient-without any debilitating illness, which showed a complete response to itraconazole 200 mg daily without any surgical intervention.